Exploration of Behavior and Needs in Reproductive Health Assistance Activities for Street Children in Semarang City - Hasrianti, Hasrianti; Shaluhiya, Zahro; Agushybana, Farid (Journal of Health Education, 2022)
Background: Street Children are children who spend or spend most of their time on the streets, markets, shops and other crowded centers. One of the problems often faced by street children is reproductive health problems. Reproductive health problems that occur in street youth are free sex, sexually transmitted infections, and HIV/AIDS. Street children need competent assistances in providing education about reproductive health. The purpose of this study was to analyze the needs and potential of assistances in providing reproductive health education for street youth. Methods: This qualitative research involved 17 subjects who accompany street children. Data collection techniques with interviews and documentation. The research was conducted in 5 institutions that assist street children, namely 1) Mandiri RSPA, 2) Indonesian Gold Foundation NGO, 3) Anantaka NGO, 4) Setara NGO and 5) Rumpin Bangio NGO. The research was conducted from January-May 2021. Results: The results showed that the assistances had good knowledge, attitudes, and practices about reproductive health. Mentoring activities can provide positive motivation to street youth and minimize social deviant behavior. Mentoring activities received support from various parties such as UNICEF and the Semarang City Social Service. Conclusion: Knowledge, attitude and behavior about reproductive health is an important capital in the implementation of reproductive health education for street children. KEYWORDS: reproductive health, street children, description of assistance behavior